Mapping crime harm and priority locations in New Zealand: A comparison of spatial analysis methods. (September 2017) - Curtis-Ham, Sophie; Walton, Darren
Abstract: Despite progress being advanced with spatial approaches to crime and crime control, the geography of crime harm has to date received little attention. The recent development of "Crime Harm Indices", which weight crimes by an estimate of the relative harm they cause, offers an opportunity to improve on volume based spatial analysis approaches to identify where crime harm concentrates. This study aims to address this issue via the use of a Crime Harm Index (CHI) developed for New Zealand. By contrast to localized 'harm-spotting' analysis, we apply a census unit based approach to identify, at a macro level, the neighborhoods and wider communities suffering the highest crime harm in New Zealand. This approach enables harm to be viewed not only as a total Index but as a rate controlled for population and allows for the identification of census based sociodemographic factors which predict harm. Specifically, this paper compares the CHI with the New Zealand Priority Locations Index (PLI), an existing census unit based crime analysis tool which combines crime and demographic variables to identify communities vulnerable to crime and disorder issues. In this study CHI and PLI scores were calculated for Census Area Units (normally containing 3000–5000 population) across New Zealand. Bivariate correlations and a general linear model were used to determine the relationships between the CHI and PLI and additional population related variables. The CHI and PLI were weakly correlated, with population size and urban/rural categorization also accounting for CHI variance. Mapping techniques are used to illustrate outlier locations where the CHI and PLI differ widely and to identify location features which may assist in explaining CHI/PLI differences. This work exemplifies a novel geographic approach to the problem of crime harm with implications for resource allocation at national through to local levels. Wider implications for the theory and practice of crime and crime harm control are discussed, along with limitations of the study and areas for further research. Highlights: A new Crime Harm Index (CHI) is applied to Census Area Units. The CHI is compared to the Priority Locations Index (PLI). The PLI measures sociodemographic vulnerability to crime. Locations identified by the PLI are often not those suffering the most crime harm.